Predictors of antiplatelet cessation in a real-world patient population undergoing non-cardiac surgery after PCI. (1st October 2022) - Koshy, Anoop N.; Cao, Davide; Levin, Matthew A.; Sartori, Samantha; Giustino, Gennaro; Kyaw, Htoo; Claessen, Bimmer; Zhang, Zhongjie; Nicolas, Johny; Camaj, Anton; Roumeliotis, Anastasios; Chandiramani, Rishi; et al.
Abstract: Background: The optimal perioperative management of antiplatelet therapy (APT) therapy in patients undergoing noncardiac surgery (NCS) following percutaneous coronary intervention (PCI) is unclear. We sought to identify predictors of APT cessation in a real-world cohort of patients undergoing NCS within 1 year of PCI. Methods: Consecutive patients undergoing PCI at a tertiary center between 2011 and 2018 were prospectively enrolled. Perioperative interruption of APT was defined as cessation of either aspirin or P2Y12 inhibitor between 1 and 14 days prior to NCS. Predictors of APT discontinuation were identified by multivariable Cox regression with stepwise selection of candidate variables. Results: A total of 1092 surgeries corresponding to 747 patients were identified. Overall, there were 487 (44.6%) preoperative antiplatelet interruptions: discontinuation of either P2Y12 inhibitors only (47.4%), aspirin only (7.9%), or both agents (44.7%). Both patient-specific risk factors (prior stroke, lower BMI, anemia, MI) and procedure specific risk factors (chronic total occlusions, multivessel disease, drug-eluting stent use) affected decisions regarding APT cessation. Likelihood of APT cessation increased in higher-risk surgeries and in patients on more potent P2Y12 inhibitors (ticagrelor/prasugrel vs clopidogrel) whereas those undergoing NCS <90 days post PCI were less likely to have cessation of APT. Conclusion: In this contemporary cohort of post-PCI patients undergoing NCS, patient-, angiographic- and surgery-specific factors all affected decision-making regarding APT cessation. Our findings reflective of real-world practice, highlight the importance of a multidisciplinary team approach to individualize decision making in these patients. Highlights: Optimal antiplatelet therapy strategy in patients undergoing surgery following percutaneous coronary intervention (PCI) is unclear. In this study of patients undergoing major non-cardiac surgery within 1 year following PCI, cessation of antiplatelet therapy occurred in half the cases. Patient-, angiographic- and surgery-specific factors all affected decision-making regarding APT cessation highlighting the importance of a multidisciplinary team approach to individualize decision making.